Role of C-Jun N-Terminal Kinases on a Stressed Epithelium: Time for Testing Isoform Specificity - Shashikanth, Nitesh; Alaidi, Osama; Basa, Lohitha; Taank, Shreya; Rao, RadhaKrishna; Seetharaman, Jayaraman (Biology (Basel, Switzerland), 2025)
Biological, physiological, and psychological stressors cause a “stress response” in our bodies. Stressors that are sensorily perceived (either acute or chronic) trigger hormonal responses from the sympathetic nervous system—the SAM and HPA axis—that effect intended organs to alert the individual. Other stressors have a direct effect on the target organ(s) of the body—e.g., physical injury and wounds, toxins, ionizing, and UV radiation. Both kinds of stressors change cell equilibrium, often leading to reactive oxygen species (ROS) accumulation and cellular damage. Among the signaling pathways involved in fighting these stressors, the c-Jun-N-terminal kinases (JNK) respond to diverse kinds of stressors. This review focuses on JNK1 and JNK2, both of which are ubiquitously present in all cell types, and attention is paid to gastrointestinal tract epithelial cells and their response—including tight junction disruption and cytoskeletal changes. We discuss the seemingly opposite roles of JNK1 and JNK2 in helping cells choose pro-survival and pro-apoptotic pathways. We examine the common features of the JNK protein structure and the possibilities of discovering JNK-isoform-specific inhibitors since, although JNK1 and JNK2 are involved in multiple diseases, including cancer, obesity, diabetes, musculoskeletal and liver disease, no cell-specific or isoform-specific inhibitors are available.